Guided Embodiment and Potential Applications of Tutor Systems in Language Instruction and Rehabilitation - Macedonia, Manuela; Hammer, Florian; Weichselbaum, Otto (Frontiers in Psychology, 2018)
Intelligent tutor systems (ITSs) in mobile devices take us through learning tasks and make learning ubiquitous, autonomous and at low cost (Nye, 2015). In this paper, we describe guided embodiment as an ITS essential feature for second language learning (L2) and aphasia rehabilitation (ARe) that enhances efficiency in the learning process. In embodiment, cognitive processes, here specifically language (re)learning are grounded in actions and gestures (Dijkstra & Post, 2015; Fischer & Zwaan, 2008; Pecher & Zwaan, 2005). In order to guide users through embodiment, ITSs must track action and gesture, and give corrective feed-back to achieve the users’ goals. Therefore, sensor systems are essential to guided embodiment. In the next sections, we describe sensor systems that can be implemented in ITS for guided embodiment.